Acute Myopericarditis Likely Secondary to Disseminated Gonococcal Infection. (12th July 2015) - Bunker, Daniel; Kerr, Leslie Dubin
Abstract : Disseminated gonococcal infection (DGI) is a rare complication of primary infection with Neisseria gonorrhoeae . Cardiac involvement in this condition is rare, and is usually limited to endocarditis. However, there are a number of older reports suggestive of direct myocardial involvement. We report a case of a 38-year-old male with HIV who presented with chest pain, pharyngitis, tenosynovitis, and purpuric skin lesions. Transthoracic echocardiogram showed acute biventricular dysfunction. Skin biopsy showed diplococci consistent with disseminated gonococcal infection, and treatment with ceftriaxone improved his symptoms and ejection fraction. Though gonococcal infection was never proven with culture or nucleic acid amplification testing, the clinical picture and histologic findings were highly suggestive of DGI. Clinicians should consider disseminated gonococcal infection when a patient presents with acute myocarditis, especially if there are concurrent skin and joint lesions.